FAILURE IN SOMATIC PAIRING OF 4TH CHROMOSOME IN CHIRONOMUS STRIATIPENNIS KIEFFER (DIPTERA: CHIRONOMIDAE) - TRILOCHAN MIDYA; SWAPNA BHADURI; PARANTAP SARKAR (The Bioscan, 2012)
Polytene chromosomes of Chironomus striatipennis Kieffer were studied in terms of pollution in natural habitats and the polytene chromosomes of the species appeared as paired homologous chromosomes of the flies in the somatic cells at interphase stage. The polytene chromosomes obtained from the flies, collected from polluted environment, exhibited asynapsis along the polytene chromosome arms. Asynapsis along the fourth polytene chromosome in this species was most prominent. The larvae grown in artificially developed polluted condition in the laboratory with addition of Cu as heavy metal in the culture medium also exhibited asynapsis of the fourth polytene chromosome and at higher dose i.e., 15 mg/kg of soil in the substratum of the culture tray the larvae showed almost complete asynapis of the fourth chromosomes. Hence, the organization of the polytene chromosome may be an index for assessing the polluting condition of the environment where the Chironomid larvae grow.